Prediction of acute cerebrovascular stroke disability using mSOAR score (Stroke subtype, Oxfordshire Community Stroke Project, age, mRS and NIHSS) - Hend Abdelghany; Mohamed Elsayed; Amgad Elmeligy; Ghada Hatem (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background Stroke is among the most prevalent causes of disability. An easy reliable tool to predict stroke outcomes will help manage neurological and non-neurological events and rehabilitation. The modified SOAR (mSOAR) score, which includes stroke subtype, Oxfordshire Community Stroke Project (OCSP) classification, age, pre-stroke modified Rankin score (mRS), and National Institutes of Health Stroke Scale (NIHSS) is simple and easily calculated prognostic tool. The objective of this research was to test the ability of the mSOAR score to predict post-stroke disability as measured by mRS at discharge and 1 month after stroke onset. Results One hundred stroke patients (aged ≥ 18 years) were included. All subjects underwent complete neurologic examination, non-contrast head computed tomography. OCSP classification, Stroke subtype, NIHSS, and mRS score on discharge and 1 month after stroke onset were assessed for all patients. The mSOAR score was significantly correlated with mRS on discharge, after 1 month of stroke, and with the length of hospital stay. mSOAR score had high sensitivity and specificity for predicting moderate-to-severe disability on discharge and after 1 month of stroke onset. Conclusion The mSOAR is an excellent and accurate tool for predicting the severity of disability on discharge and 1-month post-stroke.